Enhanced Photocatalytic Oxygen Evolution by Crystal Cutting. (20th January 2013) - Sun, Min; Xiong, Shijie; Wu, Xinglong; He, Chengyu; Li, Tinghui; Chu, Paul K.
<x xml:space="preserve">Abstract</x> Uniformly cut In2O3 truncated octahedrons are fabricated on a large scale by a simple chemical vapor deposition (CVD) technique. This theoretical analysis predicts that the emergence of {100} facets on the In2O3 truncated octahedrons enhances oxygen evolution significantly in photocatalysis and experimental photoelectrochemical measurements are consistent. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>